A Clinico-histopathological Correlation of Elective Abdominal Hysterectomy in University Hospital - Shrestha, Sarada Duwal; Shrestha, R.; Pradhan, R. (Journal of Karnali Academy of Health Sciences, 2018)
Introduction: The objective of this study was to correlate preoperative indications of abdominal hysterectomy with histopathological findings. Methods: This cross-sectional study was conducted in Patan Hospital from April 2016 to March 2018 in all the patients who underwent elective abdominal hysterectomy. Demographic characteristics, clinical symptoms, preoperative diagnosis and final histopathological diagnosis were studied. Preoperative indications were correlated with histopathological diagnosis. Results: A total of 203 elective abdominal hysterectomies were performed. Menorrhagia was the leading symptom found in 67 (33.00%) patients followed by pain abdomen in 62 (30.54%) patients. Leiomyoma was the most common preoperative diagnosis seen in 105 (51.72%) patients followed by ovarian tumor in 34 (16.75%) patients. The most common histopathological diagnosis was leiomyoma observed in 87 (42.86%) patients followed by ovarian tumor in 35 (17.24%) patients. Clinical and histopathological correlation was 100% in cases of ovarian tumor, complex endometrial atypical hyperplasia, pelvic inflammatory disease (PID), fibroid polyp and chronic cervicitis. Only 40% of preoperatively diagnosed postmenopausal bleeding cases were correlated histopathologically while the rest were missed preoperatively which included endometrial polyp (40%) and adult granulosa cell tumor (20%). Conclusions: Leiomyoma was the most common preoperative and histopathological diagnosis. Clinical and histopathological correlation was 100% in cases of ovarian tumor, complex endometrial atypical hyperplasia, PID, fibroid polyp and chronic cervicitis.